Solitary pulmonary metastases at first recurrence of osteosarcoma: presentation, treatment, and survival of 219 patients of the Cooperative Osteosarcoma Study Group - Mettmann, Vanessa; Baumhoer, Daniel; Bielack, Stefan S.; Blattmann, Claudia; Friedel, Godehard; von Kalle, Thekla; Kager, Leo; Kevric, Matthias; Nathrath, Michaela; Sorg, Benjamin; Dürken, Matthias; Hecker-Nolting, Stefanie (Cancer medicine, 2023)
Background To evaluate patient and tumour characteristics, treatment and their impact on survival in patients with a solitary pulmonary metastasis at first relapse of high-grade osteosarcoma. Procedure Two-hundred and nineteen consecutive patients who had achieved a complete surgical remission and then developed a solitary pulmonary metastasis at first recurrence of high-grade osteosarcoma were retrospectively reviewed. Results Two hundred and three (94.9%) of 214 patients achieved a second complete remission. After a median time from initial diagnosis of osteosarcoma to first relapse of 2.3 years (range, 0.3-18.8 years), actuarial post-relapse overall survival after 2 and 5 years was 72.0% and 51.2%. Post-relapse event-free survival was 39.1% and 31.1%. Median follow-up time was 3.2 years (range, 0.1-29.4 years). A longer time until first relapse and diagnosis due to imaging were positive prognostic factors in uni- and multivariate analyses, as were a second complete surgical remission and, in regard to death, the absence of a subsequent relapse. The use of salvage chemotherapy and radiotherapy were not associated with patient outcomes, nor was the surgical approach (thoracoscopy vs. thoracotomy) nor the exploration (uni- vs. bilateral). Conclusion Approximately half of the patients who experience a solitary pulmonary relapse at first recurrence of osteosarcoma remain alive 5 years after this first relapse. Only one third will remain disease-free. A complete surgical resection of the lesion is essential for long-term survival while relapse chemotherapy does not seem to improve survival. Innovative therapies are required to improve outcomes.
Online veröffentlicht: 7. August 2023
Gesehen am 01.08.2024